2020
DOI: 10.1101/2020.01.25.919795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-11 is a Marker for Both Cancer- and Inflammation-Associated Fibroblasts that Contribute to Colorectal Cancer Progression

Abstract: 42Interleukin (IL)-11 is a member of the IL-6 family of cytokines and involved in multiple 43 cellular responses, including tumor development. However, the origin and functions of 44 IL-11-producing (IL-11 + ) cells are not fully understood. To characterize IL-11 + cells in 45 vivo, we generated Il11 reporter mice. IL-11 + cells appeared in the colon of three murine 46 tumor models, and a murine acute colitis model. Il11ra1 or Il11 deletion attenuated the 47 56 57 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
0
0
Order By: Relevance
“…This hypothesis is further supported by several other mammalian studies that have reported a proregenerative role for the components of IL-6 family/STAT3 signaling after tissue damage (27,(63)(64)(65)(66). Furthermore, in the zebrafish heart, we found that endocardial Stat3 activation after injury depended on Il-11 signaling, while in mammals, it was reported that stimulation with IL-11 only resulted in a transient Stat3 activation for various cell types in vitro (67,68). This hypothesis may explain in part why nonregenerative species do not form a blastema after injury, but in contrast predominantly display myofibroblast activation and scar formation, highlighting the need for a deeper comparative investigation of the mechanisms downstream of IL11RA/Il11ra activation in regenerative and nonregenerative species.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is further supported by several other mammalian studies that have reported a proregenerative role for the components of IL-6 family/STAT3 signaling after tissue damage (27,(63)(64)(65)(66). Furthermore, in the zebrafish heart, we found that endocardial Stat3 activation after injury depended on Il-11 signaling, while in mammals, it was reported that stimulation with IL-11 only resulted in a transient Stat3 activation for various cell types in vitro (67,68). This hypothesis may explain in part why nonregenerative species do not form a blastema after injury, but in contrast predominantly display myofibroblast activation and scar formation, highlighting the need for a deeper comparative investigation of the mechanisms downstream of IL11RA/Il11ra activation in regenerative and nonregenerative species.…”
Section: Discussionsupporting
confidence: 89%
“…While mild UC patient's exhibit increased IL-11 expression, severe UC patients show a decrease in expression [277]. A study using a human cancer database found that genes enriched in IL-11+ fibroblasts were elevated in human colorectal cancer, and the high expressions of several of these genes correlated with a reduced disease-free survival rate in colorectal cancer patients [278]. Previous studies have demonstrated that IL-11+ cells are derived from stromal or epithelial cells [53,158].…”
Section: Interleukin-11mentioning
confidence: 99%
“…There is substantial evidence that IL-11 regulates tumor progression, cellular growth, and differentiation. While IL-11 has been suggested to become a therapeutically important molecule in the supportive care of cancer patients receiving chemotherapy [278], the study indicates that IL-11 may upregulate colorectal carcinoma cell growth and/or invasion, necessitating cautious attention to the therapeutic use of IL-11 [279]. Table 3 contains detailed description of interleukin families involved in CRC and their potential therapeutic strategies.…”
Section: Interleukin-11mentioning
confidence: 99%